2017
DOI: 10.20959/wjpps20175-9107
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Possible Risk Factors Associated With Overweight and Obesity Among Adults in Mayo Area in Khartoum State-Sudan

Abstract: This is a descriptive cross -sectional community based study, was carried out among adults in Mayo area in Khartoum State -Sudan, aims to estimate the prevalence of and to identify the possible risk factors associated with overweight and obesity among adults. Data were collected from 397 participants (57.7% females and 42.3% males). Using a pre tested structured questionnaire to collect sociodemographic characteristics such as (Sex, age group, marital status, monthly income, educational level, and family histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…This study revealed that the respondents who spent their time watching TV or films, playing games, using the computer or internet, sitting at a desk, sitting with friends, traveling in a car, or reading greater or equal to 181 minutes a day were more likely to be overweight or obese. This finding is in line with a study among adults in the Mayo area in Khartoum State-Sudan and a study among women in Addis Ababa [20,28]. This might be explained that sedentary behavior increases physical inactivity.…”
Section: Plos Onesupporting
confidence: 92%
See 4 more Smart Citations
“…This study revealed that the respondents who spent their time watching TV or films, playing games, using the computer or internet, sitting at a desk, sitting with friends, traveling in a car, or reading greater or equal to 181 minutes a day were more likely to be overweight or obese. This finding is in line with a study among adults in the Mayo area in Khartoum State-Sudan and a study among women in Addis Ababa [20,28]. This might be explained that sedentary behavior increases physical inactivity.…”
Section: Plos Onesupporting
confidence: 92%
“…This finding is supported by EDHS reports of 2016 [18]. Similarly, the studies in Sudan, Dar as Salaam-Tanzania, United States, and Benin reported a higher proportion of overweight or obesity among females than men [20,22,29,44]. The variation might be explained by different distribution in risk factors (e.g., biological variation-women gain weight during menopause, physical activity, and work intensity) between women and men across the community [46,47].…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations